PERFORMANCES OF INDIAN POSTAL SERVICES - ANAND.M.B; D L, SRINIVAS; RAMESH, H H (Innovare Journal of Business Management, 2013)
The Indian Postal Service, with 155,333 post office, is the most widely distributed post office system in the world. The global economic and financial crisis has further deteriorated the conditions in mail markets, with postal operators losing up to 20percent of their mail traffic during this two-year economic downturn, and forecasting losses of 30 percentÂ over the next decade that could leave the industry with large excess capacities. India Post provides accessible and affordable service to Â Â the people of India through its unparalleled network of post offices. Mails, POSB PLI, and Parcel are the mainstay of post offices with several new services like money transfer, EMO and distribution of mutual funds taken successfully in the last decade. Due to itsÂ Â competitive advantage of geographical accessibility and its time tested accounting procedures,Â India post has also positioned itself as a reliable agency for the Government of India (in implementing its inclusive growth policies. To improve its service quality and operational efficiency, India post has introduce a centralized core banking solution with alternate delivery channels facilitating any time any where banking environment. This core banking environment will enable faster transfer of funds and easier withdrawals. The alternate delivery channels planned for service delivery are ATMs, Internet, Phone, SMS and Mobile Banking. This paper explore the growth and performance of Postal services and future opportunities in India.